Designing Creative Economy through Community-based Ecotourism: A Case Study of Youtefa Bay Park, Jayapura, Indonesia - Akhmad Kadir; Pawenari Hijjang; Fredrik Sokoy; Matias Benoni Mano (JSW (Jurnal Sosiologi Walisongo), 2025)
Efforts to enhance a creative economy via community-based ecotourism are vital for regional development. Using a qualitative method, this study examines the state of ecotourism, indigenous community involvement, and the challenges faced in fostering creative economy practices in Youtefa Bay Park. The findings highlight the area's potential to boost the local economy through ecotourism that integrates indigenous knowledge, exploiting its natural beauty, cultural assets, and historical heritage. Collaborative management involving the government, private sector, and local communities is essential for sustainable growth. The study emphasizes the need for local regulations and initiatives to increase regional income and development, demonstrating ecotourism's role as a driver for economic and cultural preservation in Papua. The collaborative model in tourism management with recognition of customary assets in Youtefa Bay has become an urgent demand for the government to establish a blueprint for inclusive and community rights-based ecotourism development policies within the framework of special autonomy.